Social inclusion and exclusion of people with mental illness in Timor-Leste: a qualitative investigation with multiple stakeholders - Teresa Hall; Ritsuko Kakuma; Lisa Palmer; Harry Minas; João Martins; Michelle Kermode (BMC, 2019)
Abstract Background Social inclusion is a human right for all people, including people with mental illness. It is also an important part of recovery from mental illness. In Timor-Leste, no research has investigated the social experiences of people with mental illness and their families. To fill this knowledge gap and inform ongoing mental health system strengthening, we investigated the experiences of social inclusion and exclusion of people with mental illness and their families in Timor-Leste. Methods Eighty-five participants from the following stakeholder groups across multiple locations in Timor-Leste were interviewed: (1) people with mental illness and their families; (2) mental health and social service providers; (3) government decision makers; (4) civil society members; and (5) other community members. Framework analysis was used to analyse interview transcripts. Results People with mental illness in Timor-Leste were found to face widespread, multi-faceted sociocultural, economic and political exclusion. People with mental illness were stigmatised as a consequence of beliefs that they were dangerous and lacked capacity, and experienced instances of bullying, physical and sexual violence, and confinement. Several barriers to formal employment, educational, social protection and legal systems were identified. Experiences of social inclusion for people with mental illness were also described at family and community levels. People with mental illness were included through family and community structures that promoted unity and acceptance. They also had opportunities to participate in activities surrounding family life and livelihoods that contributed to intergenerational well-being. Some, but not all, Timorese people with mental illness benefited from disability-inclusive programming and policies, including the disability pension, training programs and peer support. Conclusions These findings highlight the need to combat social exclusion of people with mental illness and their families by harnessing local Timorese sociocultural strengths. Such an approach could centre around people with mental illness and their families to: increase population mental health awareness; bolster rights-based and culturally-grounded mental health services; and promote inclusive and accessible services and systems across sectors.